Use-Dependent Removal of the 4-Aminopyridine-Induced Block of the Transient K+ Current in Rat Dorsal Root Ganglia - Yoshiaki Ohishi; Tomoya Matsutomi; Taixing Zheng; Jun-ichi Kakimura; Hiroshi Maruyama; Nobukuni Ogata (Elsevier, 2003)
Effects of 4-aminopyridine (4-AP) on the transient K+ current (IA) was studied in rat sensory neurons using the whole cell patch-clamp technique. The amplitude of IA was reduced by 4-AP. The steady-state inactivation curve for IA was shifted in the positive direction by 4-AP, suggesting that the blocking action of 4-AP may be attenuated by membrane depolarization. When two IAs were evoked with variable intervals, the peak amplitude of the IA induced by the second pulse was augmented in the presence of 4-AP. These results indicate that the action of 4-AP can be modulated by concurrent neuronal activities.